Adverse events of coblation or microdebrider in pediatric adenoidectomy: A retrospective analysis in 468 patients - Tiancong Liu; Chao Ji; Yang Sun; Weiliang Bai (Laryngoscope Investigative Otolaryngology)
Abstract Objective Childhood obstructive sleep apnea hypopnea syndrome (OSAHS) is a common clinical disease that can cause serious complications if not treated in time. Adenoidectomy with or without tonsillectomy is the most important first line surgical treatment of obstructive sleep apnea in children. The aim of this study was to compare the differences between these two surgical procedures for adenoidectomy in terms of operation time, intraoperative blood loss, proportion of patients experiencing postoperative delayed hemorrhage, and incidence of adverse events. Study Design Retrospective analysis. Methods We performed a retrospective systematic analysis of patient data using the in‐house electronic patient records and considered a 2‐year period from 2016 to 2017. In total, 468 patients who underwent adenoidectomy under nasal endoscopy with coblation or microdebrider were identified. Results The coblation adenoidectomy technique was associated with significantly reduced blood loss and operation time. However, incidence of fever, neck pain, and halitosis were significantly lower in the microdebrider adenoidectomy group (p < .01). The difference in the postoperative primary and secondary hemorrhage between the two groups was not statistically significant (p > .05). Conclusion Coblation adenoidectomy had a significantly higher incidence of adverse events such as halitosis, neck pain, and fever. Therefore, otorhinolaryngologists should consider the differences in adverse events when selecting use of coblation adenoidectomy for pediatric patients. Level of Evidence IV